Enhancing English Language Acquisition in Young Learners Through Experiential Learning Activities - Amanah, Ainun; Ratna Sari Dewi; Fahriany (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study examines the perspectives of two English teachers at SEED Academic on the use of experiential learning in teaching young learners. Using a qualitative descriptive case study approach, data were collected through semi-structured interviews and classroom observations. The research aimed to explore how teachers conceptualize experiential learning, the strategies they use to implement it, and the challenges they face in doing so. The current study made advantage of a qualitative descriptive instrument. According to the study, teachers employed different methods to teach English to young learners and had different opinions regarding how to use experiential learning. It also found that implementing experienced learning proved challenging for educators. Findings reveal that experiential learning promotes student engagement, creativity, and real-world application of language skills. However, teachers also reported challenges such as time constraints and managing diverse learning needs. The study recommends greater support for English teachers in implementing experiential learning to enhance student-centered language education in primary settings. Nonetheless, a teacher has already included practical learning into several English language teaching exercises. Through encouraging critical thinking and creativity, experiential learning helps students to apply their knowledge in relevant settings. Incorporating practical learning into English language instruction helps young students acquire their language far better. All things considered, using experiential learning to teach English to young kids was advantageous. Consequently, the study advises English teachers to use experiential learning since it offers empirical data supporting its adaption in primary-level language classrooms and shows how interactive, real-world events can raise students' participation and learning results.